2018
DOI: 10.1007/s00240-018-1051-0
|View full text |Cite
|
Sign up to set email alerts
|

Results of minimally invasive surgical treatment of allograft lithiasis in live-donor renal transplant recipients: a single-center experience of 3758 renal transplantations

Abstract: Allograft lithiasis is a rare urologic complication of renal transplantation (RT). Our aim is to present our experience with minimally invasive surgical treatment of allograft lithiasis in our series of live-donor renal transplant recipients. In a retrospective analysis of 3758 consecutive live-donor RTs performed in our center between November 2009 and January 2017, the results of minimally invasive surgery for the treatment of renal graft lithiasis diagnosed at follow-up were evaluated. Twenty-two (0.58%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Most recently, Sarier et al reported the use of minimally invasive surgical treatment of allograft lithiasis in 22 patients, including cystolitholapaxy, flexible and semirigid ureteroscopy, and PCNL, with no major postoperative complications and a stone-free rate of 89%. 15 There are some limitations to our study. Stone analysis data were only reported in 5 out of 18 patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most recently, Sarier et al reported the use of minimally invasive surgical treatment of allograft lithiasis in 22 patients, including cystolitholapaxy, flexible and semirigid ureteroscopy, and PCNL, with no major postoperative complications and a stone-free rate of 89%. 15 There are some limitations to our study. Stone analysis data were only reported in 5 out of 18 patients.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12] However, the continued advancement in endoscopic technology has made ureteroscopy more feasible. [13][14][15] Toward this end, we report our experience with ureteroscopy for the treatment of urolithiasis in the transplant kidney and ureter.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are no established criteria for surgical treatment of allograft lithiasis, 12,13 urologists tend to adapt guidelines approved for the management of urolithiasis in the general population, with the endourological approach becoming increasingly performed. 12 In this study, the efficiency of a minimally invasive approach was observed, since all graft stones patients were treated with a PNL (one patient) or a combined approach (two patients), and all but one were rendered completely stone free.…”
Section: Discussionmentioning
confidence: 99%
“…The management of allograft lithiasis is the same whether it occurs de novo or is donor-gifted. Renal transplant lithiasis is often asymptomatic, which may be due to denervation of the graft [51,52]. The most common symptoms associated with posttransplant urolithiasis are unexplained fever, elevated Cr level, reduced urine output, and hematuria.…”
Section: Allograft Urolithiasismentioning
confidence: 99%
“…In a study by Dadkhah et al [53] comparing 2 UNC techniques, it was reported that the posterolateral extravesical UNC technique can be used to achieve easy and safe access to the upper urinary tract in kidney transplant recipients. In a series presented by Sarier et al [52], renal pelvic stones were easily removed from 2 pa-tients' transplanted kidneys using the modified Lich-Gregoir technique performed with only rigid URS without the need for flexible URS because a suitable passage to the upper urinary tract was established.…”
Section: Allograft Urolithiasismentioning
confidence: 99%